2021
DOI: 10.3390/ijms221910769
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Folliculogenesis and Uterine Endometrial Receptivity after Intermittent Vaginal Injection of Recombinant Human Follicle-Stimulating Hormone in Infertile Women Receiving In Vitro Fertilization and in Immature Female Rats

Abstract: The uterine first-pass effect occurs when drugs are delivered vaginally. However, the effect of vaginally administered recombinant human follicle-stimulating hormone (rhFSH) on ovarian folliculogenesis and endometrial receptivity is not well established. We aimed to compare the efficacy of rhFSH administered vaginally and abdominally in clinical in vitro fertilization (IVF) treatment, pharmacokinetic study, and animal study. In IVF treatment, the number of oocytes retrieved, endometrial thickness and uterine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ]. Thus, a personalized IVF treatment with fine-tuning of the Gn dose in accordance with each individual’s ovarian response has become a safe and effective practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ]. Thus, a personalized IVF treatment with fine-tuning of the Gn dose in accordance with each individual’s ovarian response has become a safe and effective practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an animal study, follicular growth and ovulation were induced more efficiently with lower frequencies of FSH injection through the vagina. Higher serum levels of progesterone and the expression of progesterone receptors in the local endometrium were also found [18].…”
Section: Introductionmentioning
confidence: 94%
“…In the pharmacokinetic study, our results showed that female subjects receiving rhFSH through vaginal administration presented with faster absorption and slower elimination. Significantly lower times of maximum observed concentration (Tmax), clearances (CL), elimination rate constants (K10), higher areas under curve (AUC), and half-lives of elimination (T 1/2 elimination) were noted, compared with those received through abdominal administration [17,18]. In the clinical parameters, we found that the female subjects receiving rhFSH using intermittent vaginal administration employing lower doses of rhFSH had similar ovarian follicle growth, mature oocytes, and pregnancy rates, compared to those who received conventional abdominal administration [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Hsu et al [ 8 ] investigated the effect of recombinant human FSH (rhFSH) on ovarian follicle and uterine parameters after abdominal and vaginal in vivo administration in infertile women receiving clinical in vitro fertilization (IVF). Detection and retrieval of mature oocytes from a human ovary is the first mandatory pre-requisite and controlled ovarian stimulation (COS) involving gonadotropin administration to stimulate the growth of multiple ovarian follicles, and it is the most effective way to increase pregnancy rates in IVF treatments.…”
mentioning
confidence: 99%